Legal mechanisms in modern port development: a critical analysis - Sheard, Clive H (Institute of Marine and Environmental Law, 2023)
The purpose of this work is to give a comprehensive picture of the legal mechanisms for running a port and how modern port development can come into conflict with the relevant aspects of traditional shipping law. In the past ten years the face of port management and administration has changed dramatically. Many port authorities are calling themselves "landlord ports", and are more interested in leasing the port than in development, maintenance and administration of port facilities. This scenario, it will be seen, clearly introduced important changes for the law relating to harbours. To get a clear understanding of this issue, I have decided to divide this work into six parts. Whenever necessary, I shall first deal with the law and related issues within the traditional concept of a port I shall then show, with illustrations where possible, the positive and negative effects of modern port development on the status quo. Most of the information concerning the basis of port administration and maritime law is derived from the works in the bibliography. Nautical publications (as listed) also provided a large portion of my illustrations as do a series of interviews, both verbal and by correspondence, with companies which operate inside port arenas.